Cobalt Chloride-induced Hypoxia Can Lead SKBR3 and HEK293T Cell Lines toward Epithelial-mesenchymal Transition - Maryam Sadri; Ali-Akbar Delbandi; Nesa Rashidi; Gholam Ali Kardar; Reza Falak (Iranian Journal of Allergy, Asthma and Immunology, 2022)
Hypoxia is a common characteristic of the tumor microenvironment. In response to hypoxia, expression of the hypoxia-inducible factor (HIF) can lead to activation of downstream molecular events such as epithelial-mesenchymal transition (EMT), invasion, and angiogenesis. In this study, CoCl2 was used to simulate hypoxia in SKBR3 and HEK293T cell lines to investigate whether this treatment can induce hypoxia-associated EMT and invasion in the studied cells. SKBR3 and HEK293T cells were treated with different concentrations of CoCl2 at different exposure times and their viability was analyzed. To confirm successful hypoxia induction, the expression levels of HIF1α and vascular endothelial growth factor A (VEGFA) mRNA were assessed. Additionally, the expression of EMT-associated markers including snail, E-cadherin, N-cadherin, and vimentin, as well as invasion-related genes including matrix metalloproteinase-2 (MMP2) and MMP9 was measured. We found that cell viability in CoCl2-treated cells was concentration-dependent and was not affected at low doses. While the expression of HIF and VEGFA genes was upregulated following hypoxia induction. E-cadherin expression was significantly downregulated in HEK293T cells; while, N-cadherin and snail were upregulated in both cell lines. Moreover, an increment of MMP expression was only observed in SKBR3 cells. Taken together, the findings indicated that CoCl2 can mimic hypoxia in both cell lines, but EMT was triggered in SKBR3 cells more effectively than in HEK293T cells, and invasion was only stimulated in SKBR3 cells. In conclusion, SKBR3 cancer cells can be used as an EMT model to better understand its control and manipulation mechanisms and to investigate new therapeutic targets for the suppression of tumor metastasis.